¿Cuáles son las revistas, libros y personas más influyentes en la biología latinoamericana? - Monge-Nájera, Julián; Benavides-Varela, Catalina; Morera, Bernal (Revista de Biología Tropical, 2004)
A survey was distributed by email to 553 biologists who study the Neotropics, in order to identify the journals, books and researchers with the greatest influence over Latin American biology. The biologists’ database of the Revista de Biología Tropical was used to obtain their addresses. One third of them answered. The Revista de Biología Tropical is considered the most influential journal in the region. The majority of other influential journals are published in developed countries. The thematic distribution of answers, as well as independent assessments found in the literature, indicate that these and other survey results are not biased by the use of the journal’s database. By subject, marine and ecological journals are the most influential. In contrast with American science, there are no researchers or books that clearly dominate the field. These results hint to the subjectivity of many awards and qualifications and possibly reflect a lack of tradition regarding appearance of local scientists in the mass media, the small capacity of world wide diffusion for local research and the low priority of science in the Iberoamerican culture. Latin American journals should improve, specially through efficient communication with authors, stringent rejection of inferior manuscripts and through widespread and timely distribution. The marked dominance by male researchers may reflect the lower number of women in the field, and social inequality. Despite the absence of “superstars”, there was a correlation: most scientists in the “list of outstanding researchers” were from large countries. The publication of the most influential journal in one of the smallest countries of the region might reflect the relatively long period of existence of the Revista (half a century), the lack of other alternatives in the region and the journal’s inclusion in international indices. Recommendations for Latin American science include a selection of the best journals to receive financial support and the establishment, with help from the mass media, of a group of selected researchers as role models for the new generations.